2011
DOI: 10.1270/jsbbs.61.61
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a novel quantitative trait locus for cold tolerance at the booting stage derived from a tropical japonica rice variety Silewah

Abstract: Cold stress at the booting stage in rice induces spikelet sterility because of aberrant microspore development, which often seriously damages seed production. Some breeding lines with high cold tolerance were developed by using tropical japonica variety Silewah as a donor of cold tolerance; however, the genetic factors that confer cold tolerance of this variety have not been comprehensively analyzed. In this study, phenotypic and molecular characterization of novel cold-tolerant strains derived from crosses wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…In this case, the spikelets covered by the flag leaf are not pollinated. Cold stress has a more direct effect on spikelet fertility because when it occurs during microsporogenesis, it causes degeneration of microspores, resulting in sterility cold stress [18]. Included in the group of cold tolerant rice genotypes for sowing Date 1 were V5 (87041-TR 990-11-2-1), V6 (88021-TR 1046-2-1-2-1), V13 (89014-TR 1134-2-2-3), V15 (89018-TR 1138-4-2-1), V18 (83025-TR 643-1-1-1-1), V35 (IR 57257-34-1-2-1), V69 (NONG 56), V162 (FANDRAPOTSY 104) and V169 (BOTRYKELY) that had high yields and good cold tolerance traits even after experiencing cold stress at the reproductive stage.…”
Section: Impact Of Cold Stress On Grain Yield and Agro-morphological mentioning
confidence: 99%
“…In this case, the spikelets covered by the flag leaf are not pollinated. Cold stress has a more direct effect on spikelet fertility because when it occurs during microsporogenesis, it causes degeneration of microspores, resulting in sterility cold stress [18]. Included in the group of cold tolerant rice genotypes for sowing Date 1 were V5 (87041-TR 990-11-2-1), V6 (88021-TR 1046-2-1-2-1), V13 (89014-TR 1134-2-2-3), V15 (89018-TR 1138-4-2-1), V18 (83025-TR 643-1-1-1-1), V35 (IR 57257-34-1-2-1), V69 (NONG 56), V162 (FANDRAPOTSY 104) and V169 (BOTRYKELY) that had high yields and good cold tolerance traits even after experiencing cold stress at the reproductive stage.…”
Section: Impact Of Cold Stress On Grain Yield and Agro-morphological mentioning
confidence: 99%
“…differences in cold tolerance). Many QTLs for cold tolerance in rice have been discovered, and they have been found on most chromosomes (except chromosome 6) using different combinations of parent cultivars; they have been found on chromosome 1 (Takeuchi et al , Andaya and Mackill , Xu et al , Kuroki et al , ), chromosome 2 (Andaya and Mackill ), chromosome 3 (Andaya and Mackill , Dai et al , Suh et al , Mori et al , Shirasawa et al ), chromosome 4 (Saito et al , , , Xu et al ), chromosome 5 (Andaya and Mackill , Xu et al ), chromosome 7 (Takeuchi et al , Xu et al , Suh et al , Zhou et al ), chromosome 8 (Kuroki et al , ), chromosome 9 (Suh et al ), chromosome 10 (Dai et al , Ye et al ), chromosome 11 (Takeuchi et al , Oh et al ) and chromosome 12 (Andaya and Mackill ). The complex nature of cold tolerance mechanisms at a molecular level is suggested by the genome‐wide distribution of these many QTLs.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular marker analysis revealed that 2 cold-tolerant strains carried chromosomal segments of Silewah at the same genomic regions on chromosomes 3, 4 and 11. Single marker analysis in segregating population confirmed that the allele of Silewah on chromosome 3 (qCTB3-Silewah) conferred cold tolerance (Mori et al, 2011). Xu et al (2008) conducted the experiment which involved 1557 BC 5 F 2 plants and their F 3 progenies grown over 2 years and they detected the eight markers which were distributed on chromosomes 1, 4, 5, 10 and 11 that were associated with cold tolerance.…”
Section: Molecular Basis Of Cold Tolerancementioning
confidence: 96%